Dielectrophoresis-Enhanced Microfluidic Device with Membrane Filter for Efficient Microparticle Concentration and Optical Detection - Young-Ho Nam; Seung-Ki Lee; Jae-Hyoung Park (Micromachines, 2025)
This paper presents a novel microfluidic device that integrates dielectrophoresis (DEP) forces with a membrane filter to concentrate and trap microparticles in a narrow region for enhanced optical analysis. The device combines the broad particle capture capability of a membrane filter with the precision of DEP to focus particles in regions optimized for optical measurements. The device features transparent indium tin oxide (ITO) top electrodes on a glass substrate and gold (Au) bottom electrodes patterned on a small area of the membrane filter, with spacers to control the gaps between the electrodes. This configuration enables precise particle concentration at a specific location and facilitates real-time optical detection. Experiments using 0.8 μm fluorescent polystyrene (PS) beads and Escherichia coli (E. coli) bacteria demonstrated effective particle trapping and concentration, with fluorescence intensity increasing proportionally to particle concentration. The application of DEP forces in a small region of the membrane filter resulted in a significant enhancement of fluorescence intensity, showcasing the effectiveness of the DEP-enhanced design for improving particle concentration and optical measurement sensitivity. The device also showed promising potential for bacterial detection, particularly with E. coli, by achieving a linear increase in fluorescence intensity with increasing bacterial concentration. These results highlight the device’s potential for precise and efficient microparticle concentration and detection.